Maternal body mass index and the prevalence of spontaneous and elective preterm deliveries in an Irish obstetric population: a retrospective cohort study. Issue 10 (15th October 2017) - Vinturache, Angela; McKeating, Aoife; Daly, Niamh; Sheehan, Sharon; Turner, Michael
Abstract : Objective: To estimate the association between maternal body mass index (BMI) and risk of spontaneous preterm delivery (sPTD) and elective preterm delivery (ePTD) in singleton and multiple pregnancies. Design: Retrospective cohort study. Setting: Electronic records of all deliveries from 2009 through 2013 in a tertiary university hospital were abstracted for demographic and obstetrical information. Participants: A total of 38 528 deliveries were included. Participants with missing data were excluded from the study. BMI was calculated from the measurement of height and weight at the first prenatal visit and categorised. Sonographic confirmation of gestational age was standard. Outcome measures: Primary outcomes, sPTD and ePTD in singleton and multiple pregnancies, were evaluated by multinomial logistic regression analyses, stratified by parity, controlling for confounding variables. Results: Overall rate of PTD was 5.9%, from which 2.7% were sPTD and 3.2% ePTD. The rate of PTD was 50.4% in multiple pregnancies and 5.0% in singleton pregnancies. The risk of sPTD was increased in obese nulliparas (adjusted OR (aOR) 2.8, 95% CI 1.7 to 4.4) and underweight multiparas (aOR 2.2, 95% CI 1.3 to 3.8). The risk of ePTD was increased in underweight nulliparas (aOR 1.8; 95% CI 1.04 to 3.4) and severely obese multiparas (aOR 1.4, 95% CI 1.02 to 3.8). Severe obesity increased the risk of both sPTD (aOR 1.4; 95% CI 1.01 to 2.1) and ePTD (aOR 1.4; 95% CI 1.1 to 1.8) in singleton pregnancies. Obesity did not influence the rate of either sPTD or ePTD in multiple pregnancies. Conclusion: Maternal obesity is an independent risk factor for PTD in singleton pregnancies but not in multiple pregnancies. Obesity and nulliparity increase the risk of sPTD, whereas obesity and multiparity increase the risk of ePTD.